Human population growth and the socioeconomic effects in warri metropolitan city Delta State Nigeria - Sajini, Faith Iwejingi (Linguistics and Culture Review, 2021)
The observable impact of population growth on socioeconomic life has become a major policy issue, especially in developing countries. This article examines the growth in human population and the socio-economic effects in Warri metropolis, Nigeria, with the specific objectives of establishing the trend in population growth from 1960-2020 using secondary data, highlighting the effects that population growth has on education, employment, and income levels, examining the effects of population growth on the socio-economic life of the inhabitants of Warri metropolis, and to make recommendations. Deriving from percentage investigation of responses, the study found that population growth exerts a considerable impact on education, employment, and income levels in the Warri metropolis. The ANOVA test outcome with p< 0.05 (0.000), led to the rejection of the first null hypothesis and the alternative hypothesis accepted, therefore there is a significant change in population across the period. The post hoc test reveals that the variations however emanated from the period between 1980 -2020. Another finding portrays that, with an R-square value of .639, that population growth expresses about 64% effect on socioeconomic life in the Warri metropolis. The study made policy-relevant recommendations that stem from the findings.